SOME ASPECTS OF MAGNETOSTRATIGRAPHIC CORRELATION - Molostovskii E.A. (My University, 1996)
The traditional visual comparison of paleomagnetic columns with the consecutive counting of magnetozones of different polarities is liable to many errors. In this approach the following methodical miscalculations are particularly apparent: the loss of an interval, an arbitrary interpolation of paleomagnetic boundaries, comparison of magnetozones of different ranks, and erroneous identification of magnetozones. Paleomagnetic stratigraphic correlation is practically impossible without exact correlation between paleontological, lithological and facies data. Appropriate examples are given to show the procedure of magnetostratigraphic correlation of marine and continental deposits in widely spaced biogeographic provinces.